Perencanaan Komunikasi Berbasis Internet pada Kementerian Agama Provinsi Jawa Tengah - Naiza Rosalia; Mutia Rahmi Pratiwi (Jurnal Riset Manajemen Komunikasi, 2022)
Abstract. The Ministry of Religion of Central Java Province has programs to reduce divorce rates, including BINWIN and KUA Kick Off in the BP4 division. However, communication activities for these programs have not been carried out massively. In line with this, the divorce rate is still increasing, it is known that it is no longer an economic problem that supports this, but a lack of mutual trust in married couples. This study aims to prepare a communication planning document for Public Relations of the Ministry of Religion for activities to communicate existing programs. The case study method with data collection techniques through interviews, documentation, and observations was carried out to obtain comprehensive data. The result of the research is the design of a communication planning document by determining the key message "Dual Roles for Family Resilience", targeted at the bride and groom and their families, aims to increase awareness of the Ministry of Religion program, the communication actor chosen is the government assisted by scholars and public figures, communication is carried out through media channels Youtube, IG and Whatsapp social networks are carried out periodically and in parallel. Abstrak. Kementerian Agama Provinsi Jawa Tengah memiliki program untuk menurunkan angka perceraian, diantaranya Kick Off BINWIN dan KUA di divisi BP4. Namun, kegiatan komunikasi untuk program-program tersebut belum dilakukan secara masif. Sejalan dengan hal tersebut angka perceraian yang masih meningkat, diketahui bukan lagi masalah ekonomi yang mendukung hal tersebut, melainkan kurangnya rasa saling percaya pada pasangan suami istri. Penelitian ini bertujuan untuk menyusun dokumen perencanaan komunikasi Humas Kementerian Agama untuk kegiatan mengkomunikasikan program-program yang ada. Metode studi kasus dengan teknik pengumpulan data melalui wawancara, dokumentasi, dan observasi dilakukan untuk memperoleh data yang komprehensif. Hasil dari penelitian ini adalah rancang bangun dokumen perencanaan komunikasi dengan menentukan pesan kunci “Peran Ganda untuk Ketahanan Keluarga”, ditujukan kepada calon pengantin dan keluarganya, bertujuan untuk meningkatkan awareness terhadap program Kemenag, pelaku komunikasi. dipilih adalah pemerintah dibantu oleh ulama dan tokoh masyarakat, komunikasi dilakukan melalui saluran media Youtube, IG dan jejaring sosial Whatsapp dilakukan secara berkala dan paralel.